2020
DOI: 10.1515/hsz-2020-0132
|View full text |Cite
|
Sign up to set email alerts
|

A role of heparan sulphate proteoglycan in the cellular uptake of lipocalins ß-lactoglobulin and allergen Fel d 4

Abstract: Lipocalins, small extracellular hydrophobic molecule carriers, can be internalized by a variety of different cells. However, to date receptors have only been identified for human lipocalins. Here, we specifically investigated uptake mechanisms for lipocalins ß-lactoglobulin and Fel d 4 in HeLa and Chinese hamster ovary (CHO) cells. We provide evidence that cell surface heparan sulphate proteoglycan is essential for internalization of these lipocalins. In HeLa cells, lipocalin uptake was inhibited by competitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Another characteristic feature of lipocalin proteins is their capacity to bind to specific cell-surface receptors ( 39 , 42 ). In humans, three groups of lipocalin receptors can be recognized ( 42 , 43 ). The group taking up the lipocalin-ligand complex in an endocytic manner includes megalin ( 44 ), the lipocalin 1-interacting membrane receptor (LIMR) ( 41 , 45 ), the lipocalin-2 receptor NGalR/24p3R ( 46 ) and basigin ( 47 ).…”
Section: Lipocalinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another characteristic feature of lipocalin proteins is their capacity to bind to specific cell-surface receptors ( 39 , 42 ). In humans, three groups of lipocalin receptors can be recognized ( 42 , 43 ). The group taking up the lipocalin-ligand complex in an endocytic manner includes megalin ( 44 ), the lipocalin 1-interacting membrane receptor (LIMR) ( 41 , 45 ), the lipocalin-2 receptor NGalR/24p3R ( 46 ) and basigin ( 47 ).…”
Section: Lipocalinsmentioning
confidence: 99%
“…For example, food allergen β-lactoglobulin (Bos d 5) was reported to be taken up by LIMR ( 206 ) which was not, however, confirmed in another study ( 207 ). Instead, β-lactoglobulin, as well as cat Fel d 4, were recently found to be internalized by the cell-surface heparan sulfate proteoglycan-mediated endocytosis in HeLa and CHO cells ( 43 ). Although these studies did not assess the allergenic capacity of lipocalins, obviously the active uptake of allergens through binding to cell-surface receptors can facilitate their access to the immune system.…”
Section: Innate Immunity In Shaping Allergen-specific Sensitization T...mentioning
confidence: 99%
“…13,14 We previously showed that the whey protein b-lactoglobulin (BLG), which is known to be a major allergen in cow's milk, loses its allergenic properties when it carries micronutrients such as flavonoid-bound iron, 15,16 vitamin A, 17 and vitamin D. 18 Dietary uptake of digestion-and protease-resistant BLG occurs through the lymphatic vessels 19,20 and is receptor-mediated. [21][22][23] Different receptors have been described as binding to it, [24][25][26][27][28][29] and there are probably also clathrin-dependent 30 mechanisms involved. Upon ingestion, BLG is associated with immune cells in the lamina propria of the intestine within minutes.…”
Section: Introductionmentioning
confidence: 99%